2019
DOI: 10.1107/s2056989018017024
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and crystal structures of [IrIII{C(CHCO2Et)(dppm)24 P,C,C′,P′}ClH]Cl·2.75CH2Cl2 and its derivatives, [IrIII{C(CHCO2Et)(dppm)24 P,C,C′,P′}(CH2CO2Et)Cl]Cl·CH3OH·0.5H2O, [IrIII{C(CHCO2Et)(dppm)24

Abstract: The common structural feature of the four title IrIII compounds is the octa­hedral coordination of the IrIII atom by a PCP pincer complex, a C atom of a (eth­oxy­oxoethanyl­idene)methane group and two variable ligands X (H, CH2CO2Et, Cl) and Y (Cl, CO).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The incorporation of CDPs and related groups in pincer‐type ligands led to the development of highly active catalysts for cross coupling reactions, [17,18] hydroamination and ‐arylation reactions [19–21] . Moreover, the two terminal binding sites of the pincer platform, often tertiary phosphines, enable the stabilization of lower oxidation states that result in electron rich transition metal complexes [12,14,30–32,22–29] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of CDPs and related groups in pincer‐type ligands led to the development of highly active catalysts for cross coupling reactions, [17,18] hydroamination and ‐arylation reactions [19–21] . Moreover, the two terminal binding sites of the pincer platform, often tertiary phosphines, enable the stabilization of lower oxidation states that result in electron rich transition metal complexes [12,14,30–32,22–29] …”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Moreover, the two terminal binding sites of the pincer platform, often tertiary phosphines, enable the stabilization of lower oxidation states that result in electron rich transition metal complexes. [12,14,[30][31][32][22][23][24][25][26][27][28][29] One of the first CDP transition metal complexes was the rhenium(VII) complex [({Ph 3 P} 2 C)ReO 3 ] + reported by Sundermeyer and co-workers. [15] In their study, the authors clearly demonstrated that CDPs are capable of stabilizing transition metal centers in high oxidation states.…”
Section: Introductionmentioning
confidence: 99%